Analysis of students problem solving ability by using polya steps in linear program material - NH Sari; S Sutiarso; S Dahlan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The purpose of this study is to analyze students problem solving ability by using polya steps in linear program material. This was a descriptive study that used a qualitative approach with 103 students of XI grade of science at SMA Negeri 1 Kota Bumi as the subject of the study. The data was collected through the technique of a written test, which consisted of two questions. The result of the research showed that the ability of problem solving in students of XI grade of science at SMA Negeri 1 Kota Bumi were good, which were 17 students or 16,50% was very good at problem solving, 53 students or 51,47% was good enough at problem solving, 28 students or 27,18% was less good at problem solving, and 5 students or 4,85% was goodless at problem solving. The results of each indicator of problem solving ability was the indicator of understanding the problem was 87,86%, indicator of arranging a plan was 45,99%, indicator of carrying out a plan was 39,31%, and indicator of re-check was 34,91%.